2001
DOI: 10.2214/ajr.177.2.1770415
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Postoperative Peripheral Nerve Lesions with High-Resolution Sonography

Abstract: In contrast to electrophysiologic tests, high-resolution sonography can show the exact location, extent, and type of a postoperative peripheral nerve lesion and the concurrent disease of surrounding tissues. Because the latter can often be the causative agent for the development of a lesion or the lack of improvement with conservative treatment, sonography yields important information that may not be obtained with other diagnostic modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0
15

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 12 publications
0
57
0
15
Order By: Relevance
“…24 Ultrasound has been shown to be an efficient, noninvasive, and low-cost method of imaging traumatic peripheral nerve pathologies. 9,10,16,21,22,24,26 After trauma, HRU can differentiate between rupture of a nerve bundle and fibroblast infiltration, which results in the formation of a traumatic neuroma. 24 Padua et al 21 showed that ultrasound was able to aid in the diagnosis or modification of the therapeutic path in 60% of patients with traumatic nerve lesions and, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Ultrasound has been shown to be an efficient, noninvasive, and low-cost method of imaging traumatic peripheral nerve pathologies. 9,10,16,21,22,24,26 After trauma, HRU can differentiate between rupture of a nerve bundle and fibroblast infiltration, which results in the formation of a traumatic neuroma. 24 Padua et al 21 showed that ultrasound was able to aid in the diagnosis or modification of the therapeutic path in 60% of patients with traumatic nerve lesions and, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3 Review of the literature shows that ultrasound is successful in clearly and accurately demonstrating complete or partial transections, nerve lacerations, epineural hematoma, and neuroma formation as well as the adequacy of postsurgical repair. 9,10,16,21,22,24,26 In this paper, we present 4 cases in which HRU accurately demonstrated the anatomy and extent of traumatic peripheral nerve injury and guided the surgical management for these patients.…”
mentioning
confidence: 99%
“…Он состоит из соединительной тка-ни, сосудов и лимфатических протоков и до-статочно плотный, чтобы отражать ультразвук, в результате чего перинервий является гипер-эхогенным. Ствол периферического нерва сос-тоит из нескольких нервных пучков и окружён толстой оболочкой -эпиневрием, который при уЗИ отображается как толстые эхогенные ли-нии [46]. В 1995 г. E. Silvestri с соавторами сообщили о явной корреляции ультразвукового и гисто-логического изображений седалищного нерва [53].…”
Section: ультразвуковые критерии повреждения периферического нерваunclassified
“…уЗИ позволяет выявить различные (до-и постганглионарные) повреждения стволов пле-чевого сплетения, в том числе и у детей [38,46]. J.R. Joseph с соавторами описали методику уЗ диагностики повреждений плечевого сплетения в неонатальном периоде после акушерских по-собий во время родовспоможения [35].…”
Section: ультразвуковые критерии повреждения периферического нерваunclassified
“…[2][3][4][5] The ability of high-frequency transducers to display neurologic structures in exquisite detail coupled with a dynamic component to the study makes sonography an attractive adjunct to clinical evaluation. 1,6 Among the upper extremity entrapment neuropathies, posterior interosseous nerve (PIN) syndrome (or supinator syndrome) has been described using magnetic resonance imaging and sonography. 7 In this condition, the PIN may be entrapped as it courses under the arcade of Frohse and enters the supinator muscle ( Figure 1).…”
mentioning
confidence: 99%